2011
DOI: 10.1128/cvi.00489-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 16 (HPV 16) and HPV 18 Antibody Responses Measured by Pseudovirus Neutralization and Competitive Luminex Assays in a Two- versus Three-Dose HPV Vaccine Trial

Abstract: Human papillomavirus 16 (HPV 16) and HPV 18 antibody responses in a 2-versus 3-dose HPV vaccine (Gardasil) trial were measured by a pseudovirus neutralizing antibody (PsV NAb) assay and by the Merck competitive Luminex immunoassay (cLIA). Eight hundred twenty-four female subjects assigned to three dosing regimens (group 1, 9 to 13 years old; 2 doses, months 0 and 6 [n ‫؍‬ 259]; group 2, 9 to 13 years old; 3 doses, months 0, 2, and 6 [n ‫؍‬ 260]; group 3, 16 to 26 years old; 3 doses, months 0, 2, and 6 [n ‫؍‬ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…3 Such potent and consistently high immune response in younger girls lead to the hypothesis that less than 3 doses of the vaccine might offer enough protection in girls aged below 15 y A number of randomized and non-randomized studies demonstrated that the antibody response elicited by 2 doses administered at least 6 months apart in adolescent girls was non-inferior to that elicited by 3 doses of the HPV vaccine. [4][5][6][7] The earliest evidence on the protective effect against infection of less than 3 doses of the vaccine was put forward by the posthoc analysis of the results of some of the phase III efficacy trials of the bivalent vaccine (2vHPV) in which some of the girls/ women received single or 2 doses by default. 8 The results also provided the early but exciting indication that even single dose of the vaccine might be effective.…”
Section: Introductionmentioning
confidence: 99%
“…3 Such potent and consistently high immune response in younger girls lead to the hypothesis that less than 3 doses of the vaccine might offer enough protection in girls aged below 15 y A number of randomized and non-randomized studies demonstrated that the antibody response elicited by 2 doses administered at least 6 months apart in adolescent girls was non-inferior to that elicited by 3 doses of the HPV vaccine. [4][5][6][7] The earliest evidence on the protective effect against infection of less than 3 doses of the vaccine was put forward by the posthoc analysis of the results of some of the phase III efficacy trials of the bivalent vaccine (2vHPV) in which some of the girls/ women received single or 2 doses by default. 8 The results also provided the early but exciting indication that even single dose of the vaccine might be effective.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to platform and format differences, these assays use different reference standards that report in different units and use serostatus cutoffs that were developed using different methods. Thus far direct comparisons between these assays have been sparse (9)(10)(11). The limited understanding of how these assays relate to each other in the context of unvaccinated populations/natural infection makes comparison across studies complex.…”
Section: Introductionmentioning
confidence: 99%
“…L1 VLP immunizations were carried out using a relatively small number of animals, and while all three constructs induced neutralizing antibodies against all three variant PsVs, the variability inherent in using small groups of animals may have concealed subtle differences in immunogenicity. Although HPV L1L2 PsVs have been used widely to monitor antibody responses to vaccines and natural infection (22,47,48,60), as well as elucidate steps in the entry process (61)(62)(63)(64), there are likely to be some differences between how these behave in vitro and how authentic HPV31 lineage variants behave in vivo, although this is a limitation of most PsV-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…A degree of vaccine-induced cross-protection against closely related genotypes, particular HPV31, HPV33, and HPV45, has also been demonstrated (16)(17)(18). HPV vaccine type-specific protection is assumed to be mediated by L1-neutralizing antibodies, which can be detected in the serum and cervicovaginal secretions of vaccinees (16,(19)(20)(21)(22). The role of L1-neutralizing antibodies in mediating cross-protection is less clear, although a recent study reported an association between the presence of HPV31 cross-neutralizing antibodies and a reduced risk of HPV31 infection (23).…”
mentioning
confidence: 99%